Traditional knowledge on medicinal plant of the Karen in northern Thailand: A comparative study - Kornkanok Tangjitman (2018)
Ethnopharmacological relevance We studied traditional medicinal plant knowledge among the Karen in northern Thailand. Aim of the study To compare traditional medicinal knowledge in 14 Karen villages in northern Thailand and determine culturally important medicinal plant species in each Karen village. Materials and methods We interviewed 14 key informants and 438 non-specialist informants about their traditional knowledge of medicinal plants. We tested normality of the data and correlations with distance to the nearest city using Kolmogorov-Smirnov tests and Spearman's rank correlation coefficient. Cluster analysis and cultural importance index (CI) were calculated for the similarity of medicinal plant used and culturally importance medicinal plant species among Karen villages respectively. Results In total 379 medicinal plant species were used. Number of medicinal plants used positively correlate with distance to the nearest city. Relatively low similarities of medicinal plant species and different CI values for species among the different areas were found. Conclusions Traditional medicinal plants still play an important role in medicinal practice of the Karen. Local environments, availability of medicinal plant and distance between Karen villages and the nearest city affect the amount of traditional medicinal knowledge in each Karen village. The medicinal plants in this study with high CI values might give some useful leads for further biomedical research. © 2013 Elsevier Ireland Ltd.